BIM2BEM for room heating-cooling time estimation after turning on the HVAC systems. Issue 1 (March 2020) - Pezeshki, Zahra; Darabi, Ahmad; Moghiman, Mohammad
Abstract: The complexity of real constructions, with irregular geometry, inhomogeneous materials, variable morphology, alterations and damages, poses numerous challenges in digital modeling and simulation of structural performances under different types of actions. Recent developments in Building Information Modeling (BIM) have introduced advanced modeling capabilities. This paper presents a new methodology using BIM2BEM for the estimation of heating and cooling time after we turn on the HVAC systems. The generation of the BIM is carried out with information of a case study model in Autodesk REVIT software. Then, BIM is turned into a Finite Element Model (FEM) in COMSOL Multiphysics software and Building Energy Modelling (BEM) is obtained in winter and summer which preserves irregularities and anomalies, such as verticality deviation and variable thickness. Afterwards, the cooling and heating time of the whole room after turning on the cooling and heating appliances was calculated and compared with reality results.